Human Waste Substitute Strategies Enhanced Crop Yield, Crop Quality, and Soil Fertility in Vegetable Cultivation Soils in North China - Bo Liu (MDPI AG, 2021)
Replacing chemical fertilizers with human waste for vegetable planting is a traditional, economical, and environmentally friendly waste resource utilization strategy. However, whether the human waste substitute strategy can improve soil fertility and increase crop yield and quality compared to the simple application of chemical fertilizers is still unclear, especially under acidic and alkaline soil conditions. In this study, we studied the effects of different ratios of human waste (urine and feces) to chemical fertilizer on the crop yield, crop quality, soil fertility, and soil chemical parameters in alkaline Cambisols and acidic Alisols cultivated with water spinach (Ipomoea aquatica Forssk.). The application variants of human waste and chemical fertilizer were as follows: (i) Control, no fertilization (CK), (ii) human waste application (HW), (iii) chemical fertilizer application (CF), (iv) 1/3 human waste to chemical fertilizer (P1), and (v) 2/3 human waste to chemical fertilizer (P2). Human waste application increased the total nitrogen, available phosphorus, available potassium, organic matter, NO3−-N, and conductivity in soil, enhanced soil enzyme activity, slowed down soil acidification, and increased the yield, soluble sugar, and vitamin C contents of the water spinach while reducing its nitrate content. Our findings indicate that human waste substitution improved soil fertility while reducing the potential risks of soil acidification, salinization, and human exposure to nitrates. These findings may be applied to increase vegetable production and quality, improve the soil environment, and increase the utilization of human waste as a valuable resource.